The UTILIZATION OF WOODEN WASTE IN INCREASING POTENTIAL TOURISM OF EMBUNG PANDAN WANGI VILLAGE EAST MAREJE - Mi'rajus Subyan Rahmat; Pyo Apriliana M; L. Aswandi Mahroni G; Eliza Ruwadah; Teddy Hartawan (E-Amal: Jurnal Pengabdian Kepada Masyarakat, 2022)
East Mareje Village with forest potential and the beauty of natural scenery and hills that have been given by God in this village, as the initial foundation carried out by the East Mareje village government to build and develop a tourist attraction in this case is the Embung Pandan Wangi area which is located in the hills of Mareje Village East. The number of dead trees in the Embung Pandan Wangi area has not been able to be utilized optimally by residents so that they are left lying around in the tourist attraction area. This is one of the concerns of the East Mareje village head in developing the natural potential of his village. The method used in this service is to provide guidance in supporting supporting facilities in the tourist area of ​​​​the pandan fragrant reservoir and training on the use of wood waste to increase the creativity of residents. The results of the implementation of service activities that have been carried out are several things that have been achieved, including: 1) Provide guidance to the people of East Mareje Village regarding the development of infrastructure facilities at the Embung Pandan Wangi tourism object by utilizing wood waste, 2) Conduct training to increase community creativity through the use of wood waste into handicraft products.